1998
DOI: 10.1017/s1431927698980576
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Considerations in Microanalysis by Energy-Dispersive Spectrometry

Abstract: X-ray counting statistics plays a key role in establishing confidence limits in composition determination by X-ray microanalysis. The process starts with measurements of intensity on one or more samples and standards as well as related background determinations. Since each individual measurement is subject to variability associated with counting statistics, it is necessary to combine all of the counting variability according to established mathematical procedures. The next step is to apply propagation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 6 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…This value is taken from a consideration of a large number of WDS measurements, in which 95% of the values were within ± 5% relative of the accepted value. Other authors suggest that, in the best case, WDS analysis is capable of a 2% relative error (Lifshin et al 1999). The latter authors did not comment on quantitative EDS measurements.…”
Section: Introductionmentioning
confidence: 99%
“…This value is taken from a consideration of a large number of WDS measurements, in which 95% of the values were within ± 5% relative of the accepted value. Other authors suggest that, in the best case, WDS analysis is capable of a 2% relative error (Lifshin et al 1999). The latter authors did not comment on quantitative EDS measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Relationship between detection limit (in oxides of Al, Ti, Ca, P, Na, Cr, Ni, Mn, Zn, Co) calculated by equation (1) The accuracy of measurement by WDS for trace as well as for major elements depends on many factors including sample preparation, the type and thickness of the coating, stability under the electron beam, accurate knowledge of the composition of the primary standards, and the quality of algorithms used for matrix (i.e., the ZAF, φ(ρz)) and interference corrections (e.g., [1,10,[45][46][47]). Jercinovic et al [10] showed that the accuracy of EPMA decreases at low concentrations because most random and systematic errors encountered during major element analysis are magnified at trace level and specific errors appear.…”
Section: Figurementioning
confidence: 99%
“…The precision of EDS depends on the X-ray counting statistics and is improved by long acquisition times [7]. Given the high number of spectra in a 3-D EDS stack, the time spent per spectrum needs to be limited to keep the total acquisition time reasonable.…”
Section: Introductionmentioning
confidence: 99%